Estimating the Parameters of a Household Production Function with Joint Products - Graham, John W.; Green, Carole A. (The Review of Economics and Statistics, 1984)
By estimating the parameters of a production function whose inputs consist of family time and market goods, the authors offer some new microeconomic estimates of the value of production that takes place in the home and also examine the concept of joint production-that is, the degree to which time devoted to home production simultaneously serves as leisure. They find evidence of substantial jointness between home production time and leisure, the degree of which is greater for wives than for husbands; and that both husband and wife possess human capital skills more productive in market work than in home work.